Proceedings of the 25th Australian Computer-Human Interaction Conference: Augmentation, Application, Innovation, Collaboration 2013
DOI: 10.1145/2541016.2541023
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable HCI for grassroots urban food-growing communities

Abstract: Mainstream food growing practices around the world call in to question our future food security, and in particular the sustainability of food consumption in urban centres. At the same time there has been a dramatic recent increase in grassroots urban food-growing communities in the UK and beyond. This paper looks at how research in sustainable human-computer interaction (HCI) can support better social and environmental practices through a focus on urban food-growing communities. In this paper we respond to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
2
31
1
Order By: Relevance
“…There are many ways to approach this problem. One could be to turn to participatory design for guidance; indeed, this is already being done (e.g., Davis, 2009;Bonanni et al, 2010;Heitlinger et al, 2013). We chose another route.…”
Section: Participation and Sustainable Hcimentioning
confidence: 99%
“…There are many ways to approach this problem. One could be to turn to participatory design for guidance; indeed, this is already being done (e.g., Davis, 2009;Bonanni et al, 2010;Heitlinger et al, 2013). We chose another route.…”
Section: Participation and Sustainable Hcimentioning
confidence: 99%
“…As part of a larger research project that explores how digital technologies can be used to support urban grassroots food-growing communities, we worked with staff, volunteers and visitors to explore key values, needs and practices of the farm [6]. Arising out of this initial stage of the research we identified opportunities for designing interactive systems to support the learning around community-based knowledge, particularly around plant knowledge.…”
Section: The Talking Plantsmentioning
confidence: 99%
“…These have a broad dominance on individually-focussed persuasive applications or "green" products (see [6] for an overview). We agree with [5] that the global environmental crisis is as much a cultural problem as an engineering one, and therefore research must engage with questions of how we understand society, "and our role in it as consumers and makers of things.…”
Section: Introductionmentioning
confidence: 99%
“…In a broader context, urban farming is seen as a grass-root initiative that helps shape sustainable urban food systems (Heitlinger et al, 2013). It does so through increasing the capacity of small-scale food producers and extending the proliferation of foodgrowing communities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Odom (2010) denotes opportunities to design interactive systems that can attract more visitors to urban farms by increasing the visibility of urban farm sites. Heitlinger et al (2013) highlight the prospect of designing for face-to-face communication within urban farms in response to the need of affection and social connectedness in interactivity. Lyle et al (2013) convey design opportunities in mitigating the vulnerability of urban farm locations in the face of natural disasters.…”
Section: Introductionmentioning
confidence: 99%